Conductive material slurry for secondary battery electrode, secondary battery electrode, and secondary battery comprising same
By using dispersants of cellulose compounds and organic acid salts in the conductive material slurry, the problem of poor dispersion of conductive materials in the slurry is solved, and the conductive performance and the energy density of the battery are improved.
Patent Information
- Application Number
- CN202380079288.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-29
- Filing Date
- 2023-11-08
- Publication Date
- 2025-06-24
AI Technical Summary
The low solubility and low dispersion of the conductive material in the existing conductive material slurry lead to insufficient conductivity, especially in secondary battery electrodes, which are difficult to improve the energy density and capacity retention rate.
Using a dispersant containing cellulose compounds and organic acid salts, the dispersion of the conductive material is improved by combining the glucose ring structure in the cellulose compounds with the surface of the conductive material, and the hydrophobic carbon chains and polar functional groups of the organic acid salts are used.
Effectively prevent the conductive material from forming a bundle-like or condensed structure in the slurry, reduce the viscosity of the slurry of the conductive material and reduce the surface resistance of the film, thereby improving the energy density and capacity retention rate of the battery and extending the battery life.
Smart Images

Figure BDA0005403302690000181 
Figure BDA0005403302690000191 
Figure BDA0005403302690000192
Abstract
Description
Technical Field
[0001] The present invention relates to a conductive material paste for a secondary battery electrode, and more particularly, to a conductive material paste for a secondary battery electrode, a secondary battery electrode, and a secondary battery including the same. Background Art
[0002] With the rapid development of the electronics, communication, and computer industries, electric vehicles, mobile phones, laptop computers, etc. are continuously achieving remarkable development, and higher requirements for energy density and stable output are put forward for batteries as the power sources for driving portable electronic devices. In particular, lithium secondary batteries, as high-performance batteries with the highest energy density among currently commercialized secondary batteries, are the most actively developed.
[0003] First, a conductive material is a material used to promote the electron movement between electrode active materials - electrode active materials or electrode active materials - current collectors, and is mainly developed centered around carbon-based materials. A conductive material paste is a solution in which the above-mentioned conductive material is dispersed in a solvent, and it becomes a material that constitutes a paste for an electrode together with an electrode active material and a binder. In recent years, with the application of secondary batteries in medium and large-sized battery markets such as electric vehicles or energy storage systems (ESS), its importance has been increasing day by day, and research on improving the theoretical capacity has also been continuously carried out.
[0004] The negative electrode of a commercial lithium secondary battery is a graphite-based material. Graphite with a layered structure exhibits excellent cycling characteristics, and the potential when lithium ions are inserted into graphite is close to the equilibrium potential of lithium. Therefore, the output voltage has no obvious difference from that when using lithium metal. However, the generally known theoretical capacity is 372 mAh / g, and there are limitations in capacitance. Therefore, as a negative electrode material with a high specific capacity and excellent cycling performance, that is, a next-generation electrode material that can replace the graphite-based negative electrode, silicon-based materials are highly anticipated.
[0005] As a negative electrode material for lithium secondary batteries, silicon has the highest theoretical capacity (4,200 mAh / g), and also has advantages such as a low potential difference with lithium, environmental friendliness, and abundant reserves. However, silicon is a non-conductor and has disadvantages in terms of durability, resulting in a decrease in capacitance. To make up for these defects, the necessity of improving the conductivity of silicon active materials or using conductive materials has become increasingly prominent.
[0006] Among them, carbon nanotubes (CNT) are rapidly becoming the main material for conductive materials. Carbon nanotubes have a nanoscale diameter and a cylindrical structure, and carbon atoms are arranged in a helical shape, with sp 2Bonding structure. Based on this structure, carbon nanotubes have attracted much attention due to their excellent physical properties such as outstanding electrical properties, strength, resilience, and thermal conductivity, and are being studied as new materials in multiple fields.
[0007] Compared with existing powdered carbon, CNT used as a conductive material for secondary batteries can improve energy density and lifespan, and can reduce the size of the battery. In particular, these advantages are more prominent in batteries for electric vehicles that require high capacity and fast charging and discharging. However, despite these excellent characteristics, the low solubility and low dispersibility of CNT are still a major problem. In particular, due to the strong Van-der Waals Force, CNT usually exists in the form of bundles or agglomerates in solution. Therefore, in the development of conductive material slurries, technical research on how to disperse the above CNT is ongoing. Summary of the Invention
[0008] Problems to be Solved by the Invention
[0009] The object of the present invention is to provide a conductive material slurry capable of uniformly dispersing a conductive material.
[0010] Another object of the present invention is to provide a conductive material slurry that can reduce the viscosity of the conductive material slurry while reducing the surface resistance of the thin film made from the conductive material slurry.
[0011] Another object of the present invention is to provide a conductive material slurry capable of adjusting the particle size of the conductive material to be smaller.
[0012] Another object of the present invention is to provide a secondary battery electrode that can improve the energy density and capacity retention rate of the battery, thereby extending its lifespan.
[0013] Another object of the present invention is to provide a secondary battery including the above secondary battery electrode.
[0014] The object of the present invention is not limited to the above-mentioned objects, and other objects and advantages of the present invention not mentioned can be understood through the following description, and can be more clearly understood through the embodiments of the present invention. In addition, it can be easily understood that the objects and advantages of the present invention can be achieved by the means and combinations thereof in the claims.
[0015] Means for Solving the Problems
[0016] According to the first aspect of the present invention for achieving the above object, there is provided a conductive material slurry for a secondary battery electrode, which comprises: a conductive material; and a dispersant; the dispersant comprises a cellulose-based compound and an organic acid salt.
[0017] According to a second aspect of the present invention, in the above first aspect, the conductive material may be one selected from the group consisting of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and combinations thereof.
[0018] According to a third aspect of the present invention, in the above second aspect, the weight ratio of the single-walled carbon nanotubes to the dispersant (single-walled carbon nanotubes: dispersant) may be from 1:1 to 1:2.
[0019] According to a fourth aspect of the present invention, in the above second aspect, the weight ratio of the multi-walled carbon nanotubes to the dispersant (multi-walled carbon nanotubes: dispersant) may be from 1:0.5 to 1:1.
[0020] According to a fifth aspect of the present invention, in any one of the above first to fourth aspects, the ratio (I d / I g ) of the maximum intensity of the D band to the maximum intensity of the G band of the conductive material obtained by Raman Spectroscopy analysis using a laser with a wavelength of 520 nm to 540 nm may be from 0.01 to 2.
[0021] According to a sixth aspect of the present invention, in any one of the above first to fifth aspects, the content of the conductive material may be less than 2.7% by weight based on the total weight of the conductive material slurry for secondary battery electrodes.
[0022] According to a seventh aspect of the present invention, in any one of the above first to sixth aspects, the weight ratio of the cellulose-based compound to the organic acid salt (cellulose-based compound: organic acid salt) may be from 1:0.15 to 1:0.5.
[0023] According to an eighth aspect of the present invention, in any one of the above first to seventh aspects, the cellulose-based compound may be one selected from the group consisting of cellulose, carboxymethyl cellulose, salts of carboxymethyl cellulose, hydroxyethyl cellulose, and combinations thereof.
[0024] According to a ninth aspect of the present invention, in any one of the above first to eighth aspects, the weight average molecular weight (M w ) of the cellulose-based compound may be 400,000 g / mol or less.
[0025] According to a tenth aspect of the present invention, in any one of the above first to ninth aspects, the weight average molecular weight (M w ) of the cellulose-based compound may be 50,000 g / mol or more and 400,000 g / mol or less.
[0026] According to the eleventh aspect of the present invention, in any one of the above first to tenth aspects, the organic acid salt may include at least one carboxylate structure containing a carboxylate and a cation.
[0027] According to the twelfth aspect of the present invention, in any one of the above first to eleventh aspects, the organic acid salt may be one selected from the group consisting of citrate, oxalate, succinate, oxalosuccinate, malate, tartrate, oxaloacetate, polyacrylate, ethylenediaminetetraacetic acid (EDTA) salt, alginate, and combinations thereof.
[0028] According to the thirteenth aspect of the present invention for achieving the above object, there is provided a secondary battery electrode including: an electrode active material; a conductive material; and a dispersant; the dispersant includes a cellulose-based compound and an organic acid salt.
[0029] According to the fourteenth aspect of the present invention, in the above thirteenth aspect, the electrode active material may include a silicon-based negative electrode active material.
[0030] According to the fifteenth aspect of the present invention, there may be provided a secondary battery including the secondary battery electrode according to the above thirteenth or fourteenth aspect.
[0031] The above technical solutions do not list all the features of the present invention. The various features of the present invention and the advantages and effects based on these features can be more detailedly understood by referring to the following specific embodiments.
[0032] Advantages of the Invention
[0033] According to one aspect (Aspect) of the present invention, there may be provided a conductive material slurry, which can reduce the viscosity of the conductive material slurry and the surface resistance of a thin film made of the conductive material slurry by adjusting the particle size of the conductive material to be smaller and uniformly dispersing the conductive material.
[0034] According to another aspect of the present invention, there may be provided a secondary battery electrode and a secondary battery including the same, which can improve the battery energy density, increase the capacity retention rate, and extend the life.
[0035] In addition to the above effects, the specific effects of the present invention will be described while explaining the specific details of implementing the present invention. Detailed Description of the Embodiments
[0036] In this specification, unless otherwise clearly distinguished and described, the description of the singular should be understood to include the plural.
[0037] When multiple embodiments are described in this specification, the effects of the present invention can be defined as including not only the effects produced by each embodiment itself, but also the effects produced by the organic combination of each embodiment. For example, even if Embodiments 1 and 2 are described separately and independently in this specification, unless otherwise clearly indicated by the context, the effects of the present invention can include the effects produced by the organic combination of Embodiments 1 and 2.
[0038] As used herein, the term "to" when referring to a numerical range means a numerical range that includes the lower and upper limit values respectively specified before or after the term. When referring to multiple numerical values for the upper or lower limit of any numerical range, the ranges disclosed herein can be understood as ranges with any one of the multiple upper limit values mentioned as its upper limit value and any one of the multiple lower limit values mentioned as its lower limit value. For example, when describing a to b or c to d in the specification, it can be understood as describing a or more and b or less, a or more and d or less, c or more and d or less, or c or more and b or less.
[0039] Degree terms used herein, such as "about" and "substantially", mean a reasonable amount of deviation of the term being modified such that the final result is not significantly changed. These terms can be interpreted to include a deviation of at least ±5% or at least ±10% provided that the deviation does not negate the meaning of the term it modifies.
[0040] In this specification, a "layer" or film can include cases where the layer or film is formed only on a part of the relevant area in addition to the case where the layer or film is formed over the entire relevant area when observing the area where the relevant layer or film exists. For example, the surface of a layer or film can be defined to include flat forms, uneven forms, and combinations thereof, or continuous forms, discontinuous forms, and combinations thereof. For example, if another member directly on top of a member is formed of a layer or film, the coverage rate of the other member with respect to the surface of the above-mentioned one member can be defined as 1% or more, 5% or more, 10% or more, 20% or more, 30% or more, 40% or more, 50% or more, 60% or more, 70% or more, 80% or more, 85% or more, 90% or more, 95% or more, or 99% or more.
[0041] In this specification, the average particle size of particles can be defined as the particle size (D 50 ) when, as measured by a laser diffraction particle size distribution measuring device, the cumulative percentage in the volume-based particle size distribution curve reaches 50%.
[0042] In this specification, the weight-average molecular weight is the molecular weight converted with standard polystyrene and can be analyzed by a gel permeation chromatography (GPC) apparatus. For example, in the GPC analysis method, the developing solvent can be tetrahydrofuran (THF), the chromatographic column can be PL Olexis of Polymer Laboratories, the sample concentration can be set to 5 mg / mL, the sample injection volume can be set to 100 μl, the flow rate can be set to 1 mL / min, the detector can be an Agilent high-temperature RI detector, and the column temperature can be set to 40 °C.
[0043] According to one aspect of the present invention, there is provided a conductive material paste for a secondary battery electrode, which includes: a conductive material; and a dispersant; the dispersant includes a cellulose-based compound and an organic acid salt.
[0044] Generally, when the solubility and dispersibility of the conductive material in the conductive material paste are low, the conductive material may exist in a bundle or aggregate structure in the paste due to strong van der Waals forces. To solve this problem, when a surfactant is used to disperse the conductive material, it is necessary to add a surfactant in an amount exceeding the content of the conductive material, which may lead to an increase in the viscosity of the conductive material paste and a decrease in the conductivity at the same time. Therefore, it is difficult to reduce the viscosity of the conductive material paste and increase its conductivity by simply using a surfactant to disperse the conductive material. For example, if a cellulose-based compound or an organic acid salt is used alone as a surfactant, since the conductive material with a long length and a high specific surface area forms a bundle or aggregate structure in the paste, it is difficult to uniformly disperse the conductive material. Therefore, as the viscosity of the conductive material paste increases and the surface resistance increases, it is also difficult to improve the conductivity between the electrode active material particles or between the metal current collectors when the above conductive material paste is applied to the secondary battery electrode.
[0045] According to one aspect of the present invention, by using a dispersant containing a cellulose-based compound and an organic acid salt, it is possible to effectively prevent the conductive material from forming a bundle or aggregate structure in the paste, thereby reducing the viscosity of the conductive material paste and the surface resistance of the film made of the conductive material paste at the same time. Specifically, the glucose ring structure in the cellulose-based compound can bind to the surface of the conductive material, and anionic structures such as carboxylate can interact with the water-based solvent, thereby providing the advantage of dispersing the conductive material. The organic acid salt has both a hydrophobic carbon chain and a polar functional group. The hydrophobic carbon chain contributes to the dispersion effect of the conductive material, and the polar functional group contributes to the good dispersion of the conductive material in the water-based solvent.
[0046] Hereinafter, the configuration of the present invention will be described in more detail.
[0047] 1. Conductive Material Slurry for Secondary Battery Electrodes
[0048] The conductive material slurry for secondary battery electrodes according to the present invention can improve the conductivity between electrode active material particles or between metal current collectors in the electrode, and includes a conductive material that minimizes the role of the binder as a non-conductor.
[0049] Specifically, the above-mentioned conductive material may be one selected from the group consisting of single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT), graphene, and combinations thereof. More specifically, it may be single-walled carbon nanotubes. The above single-walled or multi-walled carbon nanotubes are linear carbon bodies that can connect electrode active material - electrode active material or electrode active material - current collector over a longer distance than powder and easily form a network structure, thus significantly contributing to improving conductivity. Therefore, compared with existing powdered carbon materials, it can improve the energy density of the battery and extend the service life of the battery. The above graphene is a two-dimensional single layer separated from graphite composed of stacked carbon layers with a hexagonal ring structure, and its thickness can be from 0.2 nm to 0.4 nm.
[0050] Specifically, the diameter of the above single-walled carbon nanotubes can be from 1 nm to 2 nm, the length can be from 1 μm to 50 μm, and the BET specific surface area (Brunauer, Emmett, Teller specific surface area) can be 700 m 2 / g to 1600 m 2 / g.
[0051] Specifically, the diameter of the above multi-walled carbon nanotubes can be from 5 nm to 10 nm, the length can be from 50 μm to 150 μm, and the BET specific surface area can be 200 m 2 / g to 1000 m 2 / g.
[0052] In particular, due to the characteristics of long length and high BET specific surface area of carbon nanotubes in the conductive material, their solubility and dispersibility in the conductive material slurry are relatively low. That is to say, carbon nanotubes may exist in a bundled or aggregated structure in the slurry due to strong van der Waals forces. To solve this problem, if a surfactant is used to disperse the conductive material, it is necessary to add a surfactant in an amount exceeding the content of the conductive material, which may lead to an increase in the viscosity of the conductive material slurry and a decrease in the conductivity. To solve the above problems, the conductive material slurry according to one aspect of the present invention can effectively prevent the conductive material from forming a bundled or aggregated structure in the slurry by using a dispersant containing a cellulose compound and an organic acid salt, thereby reducing the viscosity of the conductive material slurry and reducing the surface resistance of the film made from the conductive material slurry.
[0053] The oxygen content of the conductive material according to the present invention can be from 0.1% to 3%. Specifically, the oxygen content of the above-mentioned conductive material can be analyzed by an EA (Elemental Analyzer) analysis device using an elemental analysis method. The oxygen content of the above-mentioned conductive material can contribute to improving the conductivity and dispersibility characteristics. When the oxygen content of the above-mentioned conductive material satisfies the above numerical range, excellent conductivity and dispersion effects can be achieved.
[0054] According to another embodiment of the present invention, the weight ratio of the above-mentioned single-walled carbon nanotubes to the above-mentioned dispersant (single-walled carbon nanotubes: dispersant) can be from 1:1 to 1:2, specifically, it can be from 1:1 to 1:1.7, and more specifically, it can be from 1:1 to 1:1.5. When the weight ratio of the above-mentioned single-walled carbon nanotubes to the above-mentioned dispersant satisfies the above weight ratio range, the formation of an aggregated structure of the single-walled carbon nanotubes can be effectively prevented, thereby reducing the viscosity of the conductive material slurry and increasing the conductivity of the conductive material slurry.
[0055] According to still another embodiment of the present invention, the weight ratio of the above-mentioned multi-walled carbon nanotubes to the above-mentioned dispersant (multi-walled carbon nanotubes: dispersant) can be from 1:0.5 to 1:1, specifically, it can be from 1:0.5 to 1:0.9, and more specifically, it can be from 1:0.5 to 1:0.8. When the weight ratio of the above-mentioned multi-walled carbon nanotubes to the above-mentioned dispersant satisfies the above weight ratio range, the formation of an aggregated structure of the multi-walled carbon nanotubes can be effectively prevented, thereby reducing the viscosity of the conductive material slurry and increasing the conductivity of the conductive material slurry.
[0056] According to still another embodiment of the present invention, the ratio of the maximum intensity of the D band to the maximum intensity of the G band (I d / I g) can be from 0.01 to 2. On the other hand, the ratio of the maximum intensity of the D band to the maximum intensity of the G band (I d / I g ) of the above conductive material can be a parameter representing the defect of the conductive material. The ratio of the maximum intensity of the D band to the maximum intensity of the G band (I d / I g ) of the above conductive material may vary depending on the type of the conductive material.
[0057] Specifically, the ratio of the maximum intensity of the D band to the maximum intensity of the G band (I d / I g ) of the above single-walled carbon nanotubes can be from 0.01 to 0.25, specifically, it can be from 0.01 to 0.2, and more specifically, it can be from 0.01 to 0.15. When the ratio of the maximum intensity of the D band to the maximum intensity of the G band (I d / I g ) of the above single-walled carbon nanotubes satisfies the above numerical range, the viscosity of the conductive material slurry can be reduced while the conductivity of the conductive material slurry can be increased.
[0058] Specifically, the ratio of the maximum intensity of the D band to the maximum intensity of the G band (I d / I g ) of the above multi-walled carbon nanotubes can be from 0.5 to 2.0, specifically, it can be from 0.5 to 1.8, and more specifically, it can be from 0.5 to 1.6. When the ratio of the maximum intensity of the D band to the maximum intensity of the G band (I d / I g ) of the above multi-walled carbon nanotubes satisfies the above numerical range, the viscosity of the conductive material slurry can be reduced while the conductivity of the conductive material slurry can be increased.
[0059] According to another embodiment of the present invention, the content of the above conductive material can be less than 2.7% by weight based on the total weight of the conductive material slurry for the secondary battery electrode, specifically, it can be from 0.5% by weight to 2.0% by weight, and more specifically, it can be from 0.5% by weight to 1.0% by weight. When the content of the above conductive material satisfies the above numerical range, the viscosity of the conductive material slurry can be reduced, and at the same time, the surface resistance of the film made of the conductive material slurry can be reduced.
[0060] The conductive material slurry for the secondary battery electrode according to the present invention contains a dispersant capable of effectively dispersing the conductive material in the slurry, thereby effectively preventing the formation of an aggregate structure of the conductive material.
[0061] The dispersant according to the present invention contains a cellulose compound and an organic acid salt. The above cellulose compound generally contains a glucose ring molecular structure and substituents in the equatorial direction bonded to the above glucose ring. Specifically, the above glucose ring molecular structure exhibits hydrophobicity and can bind to the surface of the above conductive material, while the above substituents in the equatorial direction contain hydrophilic functional groups and can form hydrogen bonds with water. The cellulose compound has a rigid property, so it can effectively disperse the conductive material in the conductive material slurry.
[0062] According to another embodiment of the present invention, the weight ratio of the above cellulose compound to the above organic acid salt (cellulose compound: organic acid salt) can be 1:0.15 to 1:0.5, specifically, it can be 1:0.3 to 1:0.5, and more specifically, it can be 1:0.4 to 1:0.5. When the weight ratio of the above cellulose compound to the above organic acid salt satisfies the above numerical range, the viscosity of the conductive material slurry can be reduced, and at the same time, the conductivity of the conductive material slurry can be increased.
[0063] For example, the above cellulose compound can be one selected from the group consisting of cellulose, carboxymethyl cellulose, salts of carboxymethyl cellulose, hydroxyethyl cellulose, and combinations thereof.
[0064] The degree of etherification (or degree of substitution; DS) of the above cellulose compound can be 0.6 to 1.2, specifically, it can be 0.6 to 1.0, and more specifically, it can be 0.6 to 0.8. The degree of etherification refers to the degree to which 3 -R groups present in one repeating unit of the above cellulose compound are replaced by carboxymethyl groups.
[0065] Specifically, the weight - average molecular weight (M w ) of the above cellulose compound can be 400,000 g / mol or less, can be 50,000 g / mol or more and 400,000 g / mol or less, and more specifically, can be 50,000 g / mol or more and 100,000 g / mol or less. The weight - average molecular weight of the above cellulose compound affects the viscosity of the conductive material slurry. The lower the weight - average molecular weight, the lower the viscosity of the conductive material slurry. When the weight - average molecular weight of the above cellulose compound satisfies the above numerical range, the conductive material can be effectively dispersed in the conductive material slurry, thereby further reducing the viscosity of the conductive material slurry and increasing the conductivity of the conductive material slurry.
[0066] The organic acid salts according to the present invention may include one or more carboxylate structures each containing a carboxylate and a cation. Specifically, they may include two or more carboxylate structures, and more specifically, three or more carboxylate structures. The more carboxylate structures containing carboxylates and cations in one molecule, the higher the solubility and dispersibility of the conductive material in the aqueous solvent. Therefore, the fluidity of the conductive material slurry can be improved, thereby reducing the viscosity of the conductive material slurry and increasing the conductivity. On the other hand, the above-mentioned cation may be, for example, one selected from the group consisting of sodium ions, lithium ions, and potassium ions.
[0067] For example, the above-mentioned organic acid salts may be one selected from the group consisting of citrate, oxalate, succinate, oxalosuccinate, malate, tartrate, oxaloacetate, polyacrylate, EDTA (ethylenediaminetetraacetic acid) salt, alginate, and combinations thereof.
[0068] According to another embodiment of the present invention, the weight ratio of the conductive material, the cellulose compound, and the organic acid salt (conductive material: cellulose compound: organic acid salt) may be 0.5 to 2.5: 0.3 to 4.0: 0.07 to 1.5. When the weight ratio of the conductive material, the cellulose compound, and the organic acid salt satisfies the above numerical range, the solubility and dispersibility of the conductive material in the conductive material slurry can be further improved, thereby reducing the viscosity of the conductive material slurry and sufficiently increasing the conductivity of the conductive material slurry.
[0069] The conductive material slurry for a secondary battery electrode according to the present invention may further include a solvent for dissolving the conductive material and a dispersant. Specifically, the above-mentioned solvent may be an aqueous solvent, and more specifically, water. The content of the solvent may be the content other than the conductive material and the dispersant with respect to the total weight of the conductive material slurry for a secondary battery electrode.
[0070] The viscosity of the conductive material slurry for a secondary battery electrode according to an embodiment of the present invention at 50 s -1 and 23 °C may be 150 cP to 1,000 cP. By reducing the viscosity of the conductive material slurry for a secondary battery electrode to the above numerical range, the effect of improving the conductivity of the conductive material can be enhanced. The viscosity of the conductive material slurry for a secondary battery electrode may be measured using an HR-2 viscometer (TA Instruments) under the following conditions, that is, the cone angle is 2°, the diameter is Φ40 mm, the shear rate is 50 s -1 , and the temperature is 23 °C.
[0071] The surface resistance of a thin film prepared using a conductive material paste for a secondary battery electrode according to an embodiment of the present invention may vary depending on the type of conductive material. When the conductive material is single-walled carbon nanotubes, the surface resistance of the above-prepared thin film may be 2.0 Ω / sq or less. When the conductive material is multi-walled carbon nanotubes, the surface resistance of the above-prepared thin film may be 20 Ω / sq or less. It is speculated that as the surface resistance of the above-prepared thin film decreases to the above numerical range, the conductive material is effectively dispersed in the conductive material paste, thereby contributing to an increase in conductivity. For example, the surface resistance of the above-prepared thin film can be measured by the four-point probe method (FPP).
[0072] 2. Secondary battery electrode
[0073] Another embodiment of the present invention described above provides a secondary battery electrode, which includes an electrode active material, a conductive material, and a dispersant, and the above dispersant includes a cellulose-based compound and an organic acid salt. Specifically, the above secondary battery electrode may be a negative electrode and may include a negative electrode current collector and a negative electrode active material layer disposed on the above negative electrode current collector.
[0074] The above negative electrode current collector can serve as a channel for transferring electrons from the outside or receiving electrons in the negative electrode active material and transferring them to the outside, enabling an electrochemical reaction to occur in the negative electrode active material. For example, the above negative electrode current collector can use materials such as copper, stainless steel, aluminum, nickel, titanium, sintered carbon, or materials with surface treatments such as carbon, nickel, titanium, and silver on the surface of aluminum or stainless steel. Specifically, transition metals such as copper and nickel that can adsorb carbon well can be used as the current collector. For example, the thickness of the above negative electrode current collector can be 6 μm to 55 μm, but the thickness of the above negative electrode current collector is not limited to this range.
[0075] The negative electrode active material layer according to the present invention may include a negative electrode active material, a conductive material, and a negative electrode binder.
[0076] The above negative electrode active material can store or release lithium ions and play a role in generating electrical energy. Specifically, the above negative electrode active material may include at least one of a silicon-based negative electrode active material and a graphite-based negative electrode active material. Specifically, it may include a silicon-based negative electrode active material. As a negative electrode material for a lithium secondary battery, the silicon-based negative electrode active material has advantages such as a high theoretical capacity, a low potential difference with lithium, environmental friendliness, and abundant reserves. However, the silicon-based negative electrode active material is a non-conductor and has disadvantages in terms of durability, with a drawback of reduced battery capacity. According to another aspect of the present invention, by mixing the above conductive material paste with the silicon-based negative electrode active material, the conductive material can be effectively dispersed in the conductive material paste, thereby increasing the conductivity of the conductive material paste. Thus, the non-conductor characteristics of the silicon-based negative electrode active material can be compensated for.
[0077] For example, the above-mentioned silicon-based active material can be selected from the group consisting of Si, SiO x (0 < x ≤ 2), Si-C composite, and Si-Y alloy (Y is an element selected from the group consisting of alkali metals, alkaline earth metals, transition metals, group 13 elements, group 14 elements, and rare earth elements).
[0078] The above-mentioned graphite-based active material can include at least one selected from the group consisting of artificial graphite, natural graphite, graphitized carbon fiber, and graphitized mesophase carbon microspheres.
[0079] For example, based on the total solid content contained in the above-mentioned negative electrode active material layer, the content of the above-mentioned negative electrode active material can be 80% to 97% by weight.
[0080] The above-mentioned negative electrode binder can inhibit the separation between negative electrode active material particles or between the negative electrode and the current collector. As the above-mentioned negative electrode binder, a polymer commonly used for electrodes in the related art can be used. As a non-limiting example, the above-mentioned negative electrode binder may include poly(vinylidene fluoride-co-hexafluoropropylene), poly(vinylidene fluoride-co-trichloroethylene), poly(methylmethacrylate), poly(ethylhexylacrylate), poly(butylacrylate), poly(acrylonitrile), poly(vinylpyrrolidone), poly(vinyl acetate), poly(ethylene-co-vinyl acetate), poly(ethylene oxide), polyacrylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl poly(vinyl alcohol), cyanoethylcellulose, cyanoethyl sucrose, pullulan, carboxyl methyl cellulose, etc., but not limited thereto.
[0081] 3. Secondary battery
[0082] Another embodiment of the present invention provides a secondary battery including the above-mentioned electrode for a secondary battery.
[0083] The secondary battery according to the present invention can provide a secondary battery, which includes: a separator; a positive electrode disposed on one surface of the separator; a negative electrode disposed on the other surface of the separator; and an electrolyte. The description of the negative electrode is repeated with the above content regarding the electrode for a secondary battery, so it is omitted here.
[0084] Separator
[0085] The porous substrate according to the present invention can provide a migration path for lithium ions while electrically insulating the negative electrode and the positive electrode to prevent short circuits, and can be a porous structure having high resistance to electrolytes and minute pore diameters.
[0086] As the constituent material of the above-mentioned porous substrate, as long as it is an organic material or an inorganic material having electrical insulation properties, there is no particular limitation. The above-mentioned porous substrate may include, for example, at least one selected from the group consisting of polyolefins, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene ether, polyphenylene sulfide, and polyethylene naphthalate. Specifically, it may include polyolefins. Polyolefins not only have excellent coating properties, but also can increase the proportion of the electrode active material layer in the battery by reducing the thickness of the separator, thereby increasing the capacity per unit volume. Specifically, the weight average molecular weight (M w ) of the above-mentioned polyolefin may be from 100,000 g / mol to 500,000 g / mol. When the weight average molecular weight of the above-mentioned polyolefin is lower than the above numerical range, it may be difficult to ensure sufficient mechanical properties, and when it exceeds the above numerical range, the shut-down function may not be achieved, or it may be difficult to mold. The shut-down function means that when the temperature of the secondary battery rises, the thermoplastic resin dissolves, thereby closing the pores of the porous substrate, blocking the migration of ions, and preventing thermal runaway of the battery.
[0087] The thickness of the above-mentioned porous substrate may be, for example, 3 μm to 50 μm or 4 μm to 30 μm. When the thickness of the above-mentioned porous substrate is lower than the above numerical range, it may be difficult to exert a sufficient conductive barrier function, and when it exceeds the above numerical range, the resistance of the separator may increase excessively.
[0088] The average diameter of the pores contained in the above-mentioned porous substrate may be, for example, 10 nm to 100 nm. A mutually connected structure may be formed between the pores contained in the above-mentioned porous substrate, so that gas or liquid can pass from one side of the porous substrate to the other side.
[0089] The separator according to another embodiment of the present invention may include a coating that improves the mechanical strength and heat resistance of the separator for secondary batteries and increases the ionic conductivity in secondary batteries, and the above coating is disposed on at least one surface of the porous substrate.
[0090] The coating according to the present invention may include an adhesive polymer and inorganic particles.
[0091] The binder polymer according to the present invention can connect inorganic particles to each other and stably fix them. For example, the above binder polymer can be selected from the group consisting of polyvinylidene fluoride-co-hexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polymethylmethacrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinylacetate, poly(ethylene-co-vinyl acetate), polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethylpullulan, cyanoethylpolyvinylalcohol, cyanoethylcellulose, cyanoethylsucrose, pullulan, carboxyl methyl cellulose, acrylonitrile-styrene butadiene copolymer, polyimide, and styrene-butadiene rubber, or a combination of two or more thereof.
[0092] According to another embodiment of the present invention, the weight ratio of the inorganic particles to the binder polymer (inorganic particles: binder polymer) can be 50:50 to 99:1, specifically, it can be 70:30 to 95:5. When the content ratio of the inorganic particles relative to the binder polymer is lower than the above numerical range, the content of the binder polymer increases, which may lead to a decrease in the performance of improving the thermal safety of the separator, and due to the reduction of the voids formed between the inorganic particles, the pore size and porosity decrease, resulting in a decrease in the performance of the final battery. When it exceeds the above numerical range, the content of the binder polymer is too low, which may lead to a weakening of the peel resistance of the coating.
[0093] The inorganic particles according to the present invention can help improve the mechanical strength and heat resistance of the separator for secondary batteries. Specifically, as long as the above inorganic particles have electrochemical stability, there is no particular limitation. That is, the inorganic particles that can be used in the present invention are not particularly limited as long as they do not undergo oxidation and / or reduction reactions within the operating voltage range of the secondary battery to which they are applied (for example, 0 to 5 V based on Li / Li + as a reference).
[0094] For example, when using inorganic particles with a high dielectric constant as the inorganic particles, it can help improve the dissociation degree of electrolyte salts, such as lithium salts, in the liquid electrolyte, thereby improving the ionic conductivity of the electrolyte solution. For the above reasons, the above inorganic particles can be inorganic particles with a dielectric constant of 5 or more, inorganic particles with lithium ion conduction ability, or a mixture thereof.
[0095] The above inorganic particles with a dielectric constant of 5 or more can be selected from the group consisting of Al2O3, SiO2, ZrO2, AlO(OH), Al(OH)3, Mg(OH)2, BaSO4, TiO2, BaTiO3, Pb(Zr x Ti 1-x )O3 (PZT, where 0 < x < 1), Pb 1-x La x Zr 1-y Ti y O3 (PLZT, where 0 < x < 1, 0 < y < 1), (1 - x)Pb(Mg 1 / 3 Nb 2 / 3 )O 3-x PbTiO3 (PMN - PT, where 0 < x < 1), HfO2, SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, and SiC, or a mixture of one or more of them.
[0096] The above inorganic particles with lithium ion conduction ability can be selected from the group consisting of lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y series glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Lix Ge y P z S w , where 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , where 0 < x < 4, 0 < y < 2), SiS2 series glass (Li x Si y S z , where 0 < x < 3, 0 < y < 2, 0 < z < 4) and P2S5 series glass (Li x P y S z , where 0 < x < 3, 0 < y < 3, 0 < z < 7)), or a mixture of two or more of the components in the group.
[0097] For example, in order to form a coating with a uniform thickness and an appropriate porosity, the average particle size (D 50 ) of the above inorganic particles can be from 1 nm to 10 μm. Specifically, it can be from 10 nm to 2 μm, and more specifically, it can be from 50 nm to 1 μm. The above "average particle size (D 50 )" refers to the particle size at the 50% point of the cumulative particle number distribution according to the particle size. The above average particle size can be measured by the laser diffraction method. Specifically, the powder to be measured can be dispersed in a dispersion medium, and then by introducing it into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), the difference in the diffraction pattern generated when the particles pass through the laser beam is measured, thereby obtaining the particle size distribution.
[0098] Specifically, the thickness of the above coating can be from 0.1 μm to 10 μm. Specifically, it can be from 1 μm to 3 μm, and more specifically, it can be from 1.4 μm to 1.6 μm. When the thickness of the above coating satisfies the above numerical range, the insulation and thermal stability of the separator can be improved, and at the same time, the energy density of the battery can be increased.
[0099] Positive electrode
[0100] The positive electrode of the present invention described above may include a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The positive electrode active material layer may contain a positive electrode active material, a conductive material, and a positive electrode binder.
[0101] For example, as the above-mentioned positive electrode current collector, as long as it has high conductivity and does not cause chemical changes in the battery, it is not particularly limited. Specifically, the above-mentioned positive electrode current collector can be made of copper, stainless steel, aluminum, nickel, titanium, sintered carbon, a material obtained by surface-treating the surface of copper or stainless steel with carbon, nickel, titanium, silver, etc., or an aluminum-cadmium alloy. The above-mentioned positive electrode current collector usually has a thickness of 6 μm to 20 μm.
[0102] For example, the above-mentioned positive electrode active material may include a lithium transition metal oxide. For example, the above-mentioned lithium transition metal oxide may be selected from the group consisting of Li x1 CoO2 (0.5 < x1 < 1.3), Li x2 NiO2 (0.5 < x2 < 1.3), Li x3 MnO2 (0.5 < x3 < 1.3), Li x4 Mn2O4 (0.5 < x4 < 1.3), Li x5 (Ni a1 Co b1 Mn c1 )O2 (0.5 < x5 < 1.3, 0 < a1 < 1, 0 < b1 < 1, 0 < c1 < 1, a1 + b1 + c1 = 1), Li x6 Ni 1-y1 Co y1 O2 (0.5 < x6 < 1.3, 0 < y1 < 1), Li x7 Co 1-y2 Mn y2 O2 (0.5 < x7 < 1.3, 0 ≤ y2 < 1), Li x8 Ni 1-y3 Mn y3 O2 (0.5 < x8 < 1.3, 0 ≤ y3 < 1), Li x9 (Ni a2 Co b2 Mn c2 )O4 (0.5 < x9 < 1.3, 0 < a2 < 2, 0 < b2 < 2, 0 < c2 < 2, a2 + b2 + c2 = 2), Li x10 Mn 2-z1 Ni z1 O4 (0.5 < x10 < 1.3, 0 < z1 < 2), Li x11 Mn 2-z2 Co z2 O4 (0.5 < x11 < 1.3, 0 < z2 < 2), Li x12 CoPO4 (0.5 < x12 < 1.3) and at least one selected from the group consisting of Li x13 FePO4 (0.5 < x13 < 1.3).
[0103] The conductive material used in the above-mentioned positive electrode may be the same as or different from the conductive material used in the above-mentioned negative electrode.
[0104] The above-mentioned positive electrode binder may be the same as or different from the above-mentioned negative electrode binder.
[0105] Electrolyte
[0106] The electrolyte according to the present invention may contain a solvent and a lithium salt.
[0107] For example, the solvent according to the present invention may be selected from one or more mixtures of the group consisting of propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone, ethyl methyl carbonate (EMC), gamma-butyrolactone (GBL), fluoroethylene carbonate (FEC), methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, amyl acetate, methyl propionate, ethyl propionate, and butyl propionate.
[0108] For example, the lithium salt according to the present invention may contain NO3 - , F - , Cl - , Br - , I - , PF6 - and other anions.
[0109] The secondary battery according to the present invention may be a cylindrical, square or pouch-type secondary battery, but as long as it is a type equivalent to a charge-discharge device, there is no particular limitation.
[0110] Another embodiment of the present invention may provide a battery module including the above secondary battery as a single cell and a battery pack including the same. For example, the above battery pack may be used as a power source for at least one medium to large-sized device selected from the group consisting of power tools; electric vehicles including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); or energy storage systems (ESSs).
[0111] Hereinafter, embodiments of the present invention will be described in more detail so that those skilled in the art can easily implement them, but this is merely an example, and the scope of the present invention is not limited to the following content.
[0112] [Preparation Example 1-1: Preparation of SWCNT Slurry]
[0113] Preparation of dispersant
[0114] 950 g of distilled water was added to a round-bottom flask, and 50 g of trisodium citrate was added, followed by stirring at room temperature for 2 hours to prepare a 5 wt% aqueous solution of trisodium citrate.
[0115] 950 g of distilled water and 50 g of carboxymethyl cellulose (CMC) for adjusting the weight average molecular weight (M w ) were added to a round-bottom flask, and the mixture was stirred at room temperature for 2 hours to prepare a 5 wt% aqueous solution of CMC.
[0116] Using the above aqueous solution of trisodium citrate and the above aqueous solution of CMC, the following conductive material slurries were prepared.
[0117] Preparation of conductive material slurry
[0118] A conductive material (SWCNT), a dispersant (aqueous CMC solution and / or aqueous citrate solution), and the remaining distilled water were added to a beaker and stirred for 60 minutes at a speed of 500 rpm to 2,000 rpm using a high-speed stirrer (Dispermat LC 55-E). The stirred product was placed in a high-pressure disperser (MN400BF, Micronox) and subjected to high-pressure dispersion under specific conditions (5 or 7 passes and 700 bar) to finally prepare an SWCNT slurry. In the case of Comparative Examples 1 to 3, passing could not be performed. In the case of Examples 1 to 11, high-pressure dispersion was carried out under the conditions of 5 passes and 700 bar, while in the case of Examples 12 to 18, high-pressure dispersion was carried out under the conditions of 7 passes and 700 bar.
[0119] On the other hand, in Tables 1, 3, 5, 7, 9, and 11 below, the remaining content was defined as distilled water.
[0120] Table 1
[0121]
[0122]
[0123] [Experimental Example 1: Evaluation of the Conductive Material Slurry of Preparation Example 1-1]
[0124] 1) Viscosity of the Conductive Material Slurry
[0125] The viscosity of the conductive material slurry prepared according to Preparation Example 1-1 was measured using an HR-2 viscometer (TA Instruments) under the following conditions: a cone angle of 2°, a diameter of Φ40 mm, a shear rate of 50 s -1 , and a temperature of 23°C.
[0126] 2) Measurement of the Surface Resistance of the Film Made from the Conductive Material Slurry
[0127] After coating the conductive material slurry on one side of a PET film using an applicator, it was dried in an oven at 90°C to prepare a film specimen (10 cm × 15 cm) with a thickness of 7 μm. The surface resistance was measured using a surface resistance meter (MCP-T700; Resistivity measurement; Mitsubishi Chemical Analytech) by the FPP method (four-probe method), and the results are listed in Table 2 below.
[0128] Table 2
[0129]
[0130]
[0131] In Table 2 above, when comparing Comparative Examples 1 to 3 with Examples 12 to 16 from the perspective of the composition of the dispersant, it can be confirmed that by using a cellulose compound and an organic acid salt as the dispersant, the viscosity of the conductive material slurry can be reduced, and the surface resistance of the thin film made from the conductive material slurry can be significantly reduced. That is, the viscosities of Comparative Examples 1 and 2 using CMC alone are very high, so passage is not possible. Similarly, Comparative Example 3 using an organic acid salt alone cannot pass due to its very high viscosity.
[0132] When comparing Examples 1 to 6 from the perspective of the ratio of the dispersant to the conductive material, when the weight ratio of SWCNT to the dispersant (SWCNT:dispersant) is 1:1 or more, it can be confirmed that the viscosity of the conductive material slurry is reduced, and the surface resistance of the thin film made from the conductive material slurry is reduced.
[0133] When comparing Examples 2 to 16 from the perspective of the ratio of the cellulose compound to the citrate in the dispersant, when the weight ratio of the cellulose compound to the citrate (cellulose compound:citrate) is 1:0.15 to 1:0.5, it can be confirmed that the viscosity of the conductive material slurry is further reduced, and the surface resistance of the thin film made from the conductive material slurry is further reduced.
[0134] When comparing Examples 1 to 18 from the perspective of the content of the conductive material, when the content of the conductive material is less than 2.7% by weight based on the total weight of the conductive material slurry, it can be confirmed that the viscosity of the conductive material slurry is further reduced, and the surface resistance of the thin film made from the conductive material slurry is further reduced.
[0135] [Preparation Examples 1-2: Preparation of SWCNT Slurry]
[0136] An SWCNT slurry was prepared in the same manner as in Preparation Example 1-1, except that CMC with a weight average molecular weight of 50,000 g / mol to 100,000 g / mol was used.
[0137] In addition, in the cases of Examples 19 to 28, 36, and 37, high-pressure dispersion was carried out under the conditions of 5 passes and 700 bar, and in the cases of Examples 29 to 35, 38, and 39, high-pressure dispersion was carried out under the conditions of 7 passes and 700 bar.
[0138] Table 3
[0139]
[0140]
[0141] [Experimental Example 2: Evaluation of the Conductive Material Slurries of Preparation Examples 1-2]
[0142] Using the same measurement method as in Experimental Example 1 above, the viscosity of the conductive material slurries of Preparation Examples 1-2 and the surface resistance of the films made from the above conductive material slurries were measured, and the results are listed in Table 4 below.
[0143] Table 4
[0144] Classification Viscosity (cP) Surface resistance (Ω / sq) Example 19 1000 3.5 Example 20 560 1.7 Example 21 485 1.3 Example 22 320 1.0 Example 23 900 3.7 Example 24 1150 3.4 Example 25 800 1.9 Example 26 680 1.7 Example 27 570 1.0 Example 28 960 3.5 Example 29 1320 3.4 Example 30 965 1.8 Example 31 900 1.3 Example 32 850 1.2 Example 33 1050 3.6 Example 34 2250 5.0 Example 35 2000 4.7 Example 36 460 1.9 Example 37 1550 3.9 Example 38 720 2.0 Example 39 1900 4.0 Example 40 1100 5.3
[0145] When comparing Table 2 and Table 4 above from the perspective of the weight-average molecular weight of CMC, it can be confirmed that by using CMC with a relatively low weight-average molecular weight (i.e., 50,000 g / mol to 100,000 g / mol), the dispersion effect of the conductive material can be improved, thereby further reducing the viscosity of the conductive material slurry and further reducing the surface resistance of the film made from the above conductive material slurry.
[0146] When comparing Examples 19 to 33 from the perspective of the ratio of the cellulose-based compound to citrate in the dispersant, when the weight ratio of the cellulose-based compound to citrate (cellulose-based compound: citrate) is 1:0.15 to 1:0.5, it can be confirmed that the viscosity of the conductive material slurry is further reduced, and the surface resistance of the film made from the above conductive material slurry is further reduced.
[0147] When comparing Examples 19 to 35 from the perspective of the content of the conductive material, when the content of the conductive material is less than 2.7% by weight based on the total weight of the conductive material slurry, it can be confirmed that the viscosity of the conductive material slurry is further reduced, and the surface resistance of the film made from the above conductive material slurry is further reduced.
[0148] When comparing Examples 19 to 24 and Example 40 from the perspective of the ratio of the dispersant to the conductive material, when the weight ratio of SWCNT to the dispersant (SWCNT: dispersant) is 1:1 to 1:2, it can be confirmed that the dispersion effect of the conductive material is further improved, thereby reducing the viscosity of the conductive material slurry and further reducing the surface resistance of the film made from the above conductive material slurry.
[0149] [Preparation Example 1-3: Preparation of SWCNT Slurry]
[0150] In the case of Examples 41 to 45, except for using CMC with a weight-average molecular weight of 400,000 g / mol and performing high-pressure dispersion under the conditions of 5 passes and 700 bar, the SWCNT slurry was prepared in the same manner as in Preparation Example 1-1.
[0151] In Examples 46 to 49, except that a conductive material having a ratio (I d / I g ) of the maximum intensity of the D band to the maximum intensity of the G band of SWCNT obtained by Raman spectroscopic analysis using a laser with a wavelength of 520 nm to 540 nm is 0.3 was used, and high-pressure dispersion was carried out under the conditions of 5 passes and 700 bar, the SWCNT slurry was prepared in the same manner as in Preparation Example 1-1.
[0152] Table 5
[0153]
[0154]
[0155] [Experimental Example 3: Evaluation of the Conductive Material Slurry of Preparation Example 1-3]
[0156] Using the same measurement method as in Experimental Example 1 above, the viscosity of the conductive material slurry of Preparation Example 1-3 and the surface resistance of the film made from the above conductive material slurry were measured, and the results are listed in Table 6 below.
[0157] Table 6
[0158] Classification Viscosity (cP) Surface resistance (Ω / sq) Example 41 2100 5.5 Example 42 1950 4.5 Example 43 1650 4.4 Example 44 1400 4.1 Example 45 2450 4.6 Example 46 340 8.0 Example 47 290 6.9 Example 48 290 7.3 Example 49 195 6.2
[0159] When comparing Tables 2, 4, and 6 from the viewpoint of the weight-average molecular weight of CMC, it can be confirmed that as the weight-average molecular weight of CMC decreases, the dispersion effect of the conductive material is further improved, so that the viscosity of the conductive material slurry is further reduced, and the surface resistance of the film made from the above conductive material slurry is also further reduced.
[0160] When comparing Examples 4, 5, 21, 22 with Examples 46 to 49 from the viewpoint of the ratio (I d / I g ) of the maximum intensity of the D band to the maximum intensity of the G band, which is a parameter indicating the defects of SWCNT, when I d / I g exceeds 0.25, although the viscosity of the conductive material slurry may decrease, it can be confirmed that the surface resistance of the film will increase excessively.
[0161] [Preparation Example 2: Preparation of MWCNT Slurry]
[0162] Except that MWCNT was used instead of SWCNT as the conductive material, the conductive material slurry was prepared in the same manner as in Preparation Example 1-1.
[0163] In the cases of Examples 50 to 56, 61 to 64, and 69 to 72, high-pressure dispersion was carried out under the conditions of 5 passes and 700 bar, and in the remaining examples, high-pressure dispersion was carried out under the conditions of 7 passes and 700 bar.
[0164] Table 7
[0165]
[0166]
[0167] [Experimental Example 4: Evaluation of the Conductive Material Slurry of Preparation Example 2]
[0168] The viscosity of the conductive material slurry of Preparation Example 2 and the surface resistance of the film made from the above conductive material slurry were measured using the same measurement method as in Experimental Example 1 above, and the results are listed in Table 8 below.
[0169] Table 8
[0170]
[0171]
[0172] When comparing Examples 51 to 56 and Examples 61 to 64 in Table 8 above from the viewpoint of the ratio of the conductive material to the dispersant, when the weight ratio of MWCNT to the dispersant (MWCNT: dispersant) is 1:0.5 to 1:1, it can be confirmed that the dispersion effect of the conductive material is further improved, thereby reducing the viscosity of the conductive material slurry and further reducing the surface resistance of the film made from the above conductive material slurry.
[0173] When comparing Examples 50, 51, 63, and 70 to 72 from the viewpoint of the ratio of the maximum intensity of the D band to the maximum intensity of the G band (I d / I g ), which is a parameter representing the defects of MWCNT, when I d / I g is between 0.5 and 2.0, it can be confirmed that the dispersion effect of MWCNT is further improved, thereby reducing the viscosity of the conductive material slurry and further reducing the surface resistance of the film made from the above conductive material slurry.
[0174] When comparing Examples 53 to 68 from the viewpoint of the ratio of the cellulose-based compound to the citrate in the dispersant, when the weight ratio of the cellulose-based compound to the citrate (cellulose-based compound: citrate) is 1:0.15 to 1:0.5, it can be confirmed that the viscosity of the conductive material slurry is further reduced and the surface resistance of the film made from the above conductive material slurry is further reduced.
[0175] [Preparation Example 3: Preparation of SWCNT Conductive Material Slurry Using Different Types of Organic Acid Salts]
[0176] Except for using succinate instead of citrate as the organic acid salt, the conductive material slurry was prepared in the same manner as in Preparation Example 1-1 for the rest.
[0177] In the cases of Examples 74 to 84, high-pressure dispersion was carried out under the conditions of 5 passes and 700 bar, and in the remaining examples, high-pressure dispersion was carried out under the conditions of 7 passes and 700 bar.
[0178] Table 9
[0179]
[0180]
[0181] [Experimental Example 5: Evaluation of the Conductive Material Slurry of Preparation Example 3]
[0182] The viscosity of the conductive material slurry of Preparation Example 3 and the surface resistance of the thin film made from the above conductive material slurry were measured using the same measurement method as in Experimental Example 1 above, and the results were then listed in Table 10 below.
[0183] Table 10
[0184]
[0185]
[0186] [Preparation Example 4: Preparation of MWCNT Conductive Material Slurry Using Different Salts]
[0187] Except for using MWCNT instead of SWCNT as the conductive material, the conductive material slurry was prepared in the same manner as in Preparation Example 3 for the rest.
[0188] In the cases of Examples 90 to 94 and 99 to 102, high-pressure dispersion was carried out under the conditions of 5 passes and 700 bar, and in the remaining examples, high-pressure dispersion was carried out under the conditions of 7 passes and 700 bar.
[0189] Table 11
[0190]
[0191] [Experimental Example 6: Evaluation of the Conductive Material Slurry of Preparation Example 4]
[0192] The viscosity of the conductive material slurry of Preparation Example 4 and the surface resistance of the thin film made from the above conductive material slurry were measured using the same measurement method as in Experimental Example 1 above, and the results were then listed in Table 12 below.
[0193] Table 12
[0194] Classification Viscosity (cP) Surface resistance (Ω / sq) Example 90 2300 33.0 Example 91 1550 25.0 Example 92 1000 18.0 Example 93 820 16.0 Example 94 1100 23.0 Example 95 1700 25.0 Example 96 1000 17.0 Example 97 850 16.0 Example 98 1000 23.5 Example 99 1300 26.0 Example 100 900 19.0 Example 101 600 18.0 Example 102 800 24.0 Example 103 1400 26.5 Example 104 950 20.0 Example 105 700 19.0 Example 106 800 25.0
[0195] Referring to Table 10 and Table 12 above, it can be confirmed that the conductive material paste using succinate and the conductive material paste using citrate show similar tendencies.
[0196] The preferred embodiments of the present invention have been described in detail above, but the scope of the present invention is not limited thereto. Various modifications and improvements made by those of ordinary skill in the technical field to which the present invention pertains, using the basic concepts of the present invention defined in the appended claims, also fall within the scope of the present invention.
Claims
1. A conductive material paste for a secondary battery electrode, characterized in that, Comprising: A conductive material; and A dispersant; The above-mentioned dispersant contains a cellulose-based compound and an organic acid salt.
2. The conductive material slurry for a secondary battery electrode according to claim 1, wherein The above-mentioned conductive material is one selected from the group consisting of single-walled carbon nanotubes, multi-walled carbon nanotubes, graphene, and combinations thereof.
3. The conductive material slurry for a secondary battery electrode according to claim 2, wherein The weight ratio of the above-mentioned single-walled carbon nanotubes to the above-mentioned dispersant is 1:1 to 1:
2.
4. The conductive material paste for a secondary battery electrode according to claim 2, wherein The weight ratio of the above-mentioned multi-walled carbon nanotubes to the above-mentioned dispersant is 1:0.5 to 1:
1.
5. The conductive material slurry for a secondary battery electrode according to claim 1, wherein The ratio of the maximum intensity of the D band to the maximum intensity of the G band of the above-mentioned conductive material obtained by Raman spectroscopy analysis using a laser with a wavelength of 520 nm to 540 nm is 0.01 to 2.
6. The conductive material slurry for a secondary battery electrode according to claim 1, wherein The content of the above-mentioned conductive material is less than 2.7% by weight based on the total weight of the conductive material slurry for a secondary battery electrode.
7. The conductive material slurry for a secondary battery electrode according to claim 1, wherein The weight ratio of the above-mentioned cellulose-based compound to the above-mentioned organic acid salt is 1:0.15 to 1:0.
5.
8. The conductive material slurry for a secondary battery electrode according to claim 1, wherein The above-mentioned cellulose-based compound is one selected from the group consisting of cellulose, carboxymethyl cellulose, salts of carboxymethyl cellulose, hydroxyethyl cellulose, and combinations thereof.
9. The conductive material slurry for a secondary battery electrode according to claim 1, wherein The weight average molecular weight of the above-mentioned cellulose-based compound is 400,000 g / mol or less.
10. The conductive material slurry for a secondary battery electrode according to claim 9, wherein The weight average molecular weight of the above-mentioned cellulose-based compound is 50,000 g / mol or more and 400,000 g / mol or less.
11. The conductive material slurry for a secondary battery electrode according to claim 1, wherein The above-mentioned organic acid salt contains at least one carboxylate structure containing a carboxylate and a cation.
12. The conductive material slurry for a secondary battery electrode according to claim 11, wherein The above-mentioned organic acid salt is one selected from the group consisting of citrate, oxalate, succinate, oxalosuccinate, malate, tartrate, oxaloacetate, polyacrylate, ethylenediaminetetraacetate, alginate, and combinations thereof.
13. A secondary battery electrode, characterized in that, Comprising: An electrode active material; A conductive material; and A dispersant; The above-mentioned dispersant contains a cellulose-based compound and an organic acid salt.
14. The secondary battery electrode according to claim 13, wherein The above-mentioned electrode active material contains a silicon-based negative electrode active material.
15. A secondary battery, wherein It includes the secondary battery electrode according to claim 13 or 14.
Citation Information
Patent Citations
Aerated warm keeping clothing
CN1061705A
Petroleum pesticide for tropical fruit tree
CN1105189A
Electronic calculator for blind person
CN1158462A
Health genseng drink and its preparing method
CN1186637A